PERAN ADVOKAT DALAM MEMBERIKAN BANTUAN HUKUM KEPADA MASYARAKAT YANG TIDAK MAMPU KORBAN TINDAK PIDANA - Rizana Rizana (Ensiklopedia Research and Community Service Review, 2026)
Abstract: An advocate is a legal professional who provides legal services, both inside and outside the court, and fulfills the qualifications stipulated under Law Number 18 of 2003 concerning Advocates. Advocates are entitled to receive honoraria for the legal services they provide. However, they are also obligated to provide free legal aid (pro bono) to indigent members of society. Individuals who are financially disadvantaged have the legal right to obtain legal assistance. To receive such legal aid, applicants who are unable to afford legal services must submit a request to an advocate acting as a legal aid provider. The Government is required to allocate funds for the implementation of legal aid through the State Budget (Anggaran Pendapatan dan Belanja Negara—APBN). In addition, regional governments may also allocate funds for the provision of legal aid to indigent communities through the Regional Budget (Anggaran Pendapatan dan Belanja Daerah—APBD). It is expected that these legal provisions will enable individuals who are unable to pay the high cost of legal representation to obtain free legal assistance when facing legal proceedings before the courts. Keywords: Advocate, Legal Aid, Victims of Criminal Offences.